Analisis Profesionalisme Guru Berdasarkan Kepemimpinan Kepala Sekolah, Budaya Sekolah Dan Motivasi Kerja (Studi pada SMP Negeri Sub Rayon 01 Kabupaten Bireuen) - Husin, Anwar (Singkite Journal, 2022)
Teachers with professional recognition are required to have personality and professional behavior in improving the quality of education. Many things make up a professional teacher. Because this is part of the competencies that teachers must have. This study limits the problem of teacher professionalism from the implications of the principal's leadership, school culture and work motivation on the teacher himself. This research is in the form of a case involving a group of teachers working in a junior high school (SMP) in Rayon 01 District, Bireuen Regency, namely 179 teachers. With this type of quantitative research and analysis tools using path analysis models. The results of the analysis found that the principal's leadership aspect had an effect on teacher professionalism by 31.05%, while school culture had an effect on 27.35%, and work motivation by 26.05%. Simultaneously these three aspects make a major contribution to the formation of teacher professionalism, which is equal to 45.2%.